Inovasi Pembelajaran Agama Islam Menggunakan Mobile Learning Quizizz di SMA Shafta Pada Era Pandemi - Lailaturrohmah Lailaturrohmah; Husniyatus Salamah Zainiyati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2020)
The essence of the title is an innovative inspiration for al-Dinul Islamic education with mobile learning quizizz at SMA SHAFTA Surabaya towards covid-19, the procedure for examining the culture of giving birth to procedures for changing policies as well as numbers covering a combination of teachers and students. In this combination, the teacher and student have other capacities and desires. Therefore, teachers and students have an appropriate understanding, there is feedback to realize educational procedures (transferring knowledge, levels, and skills as desired). Problems are always proven when education is running, not only for teachers but also for students. In this study, researchers focused on: 1) What are the problems of Islamic Education Teacher at SHAFTA SMA Surabaya? 2) How are the efforts to solve the problems of Islamic Education Teachers in SMA SHAFTA Surabaya?